Tinjauan Hukum tentang Peralihan Hak Atas Tanah melalui Perjanjian Gadai di Bawah Tangan - M. Teguh Pulungan; Muazzul Muazzul (Universitas Medan Area, 2017)
Legal Review of Transition of Land Rights Through The Gift Agreement Under HandsAbstractThe aim of research is basically about what the legal consequences of the transfer of land rights are through the underhanded pawning agreement and the application of the law to the transfer of land rights through a pawn agreement under the hand. To discuss these issues, research is carried out in the literature and by carrying out case studies on the decisions of civil cases no. 13 / PDT.G / 2011 / PN-LP. A scientific study can be believed to be true if it is arranged with the right method. Arrangement of liens on the building land is contained in customary law, as well as liens for agricultural land regulated also by customary law, except for the return and redemption of land regulated by article 7 of Law No. 56 Prp 1960. Withdrawal of conclusions based on the results of the study of the case is the regulation of liens on the building land contained in customary law, as well as liens for agricultural land regulated also by customary law, except for the return and redemption of land.